A comparison of general and explicit delay cues to reinforcement for tangible-maintained challenging behaviour. (2nd November 2015) - Hong, Ee Rea; Neely, Leslie; Rispoli, Mandy J.; Trepinski, Tonya M.; Gregori, Emily; Davis, Tonya
Abstract: Objectives : This compares effects of explicit delay cue to reinforcement to general delay cue to reinforcement when attempting to decrease tangible-maintained challenging behaviours of children with autism spectrum disorder (ASD). Methods : Two school-age children with ASD participated in this study. In order to evaluate the effects of a general cue versus an explicit cue on the participants' tangibly maintained challenging behaviours, a multiple baseline design across settings with an embedded alternating treatments design was used. Results : Results suggested that both types of delay cue to reinforcement demonstrated effectiveness on decreasing tangible-maintained behaviours of the participant. For both participants, an explicit delay cue demonstrated slightly better effects on the participants' challenging behaviours then a general delay cue. Conclusions : This study adds an evidence to support that delayed reinforcement can be used as an effective strategy to reduce both escape and tangible-maintained challenging behaviours of children with ASD across multiple settings.